Predicting crime using deep learning - Shihab, Muhammad Nafees; Chowdhury, Anupam; Mahmood, SK. Belayet (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.